Transparent optical wireless hubs using wavelength space division multiplexing - Liang, K; Shi, H; Sheard, S; O'Brien, D (2004)
In this paper we describe a novel scheme that uses wavelength space division multiplexing to provide high bit rate communications using indoor line of sight (LOS) optical links. In the approach, a dispersive grating, or more complex diffractive optics, is used for passive beam steering. Light from a ceiling mounted hub is steered to a corresponding Mobile Terminal (MT) within a cell in the coverage area, depending on the wavelength that illuminates the dispersive element. The hubs can be optically transparent, passive and theoretically reciprocal. An identical or similar dispersive component can be used in the transceivers at both ends of the hub uplink and downlink. The hubs have the potential to provide data rates of Gbits/s, terminal mobility as well as low complexity. In order to test the concept a one-dimensional (1D) system has been fabricated. A simple 1st order plane diffraction grating with a pitch of 1.1 μm is used to provide 1D beam steering. A dispersive angle of approximately 10 degrees over a wavelength range of 30nm in the wavelength division multiplexing (WDM) 'C band (1530nm - 1560nm) is obtained. Simulation shows that the dispersive angle can be further increased up to 90 degrees using a secondary optical system. Transmission of 1Gb/s data has been demonstrated using this initial configuration. In the paper we discuss these results and further refinement to the system.